Obstetric emergencies during the COVID-19 lockdown period: a case series - Vasudhar, Ananya; S., Anita; Patil, Gayatri L.; S., Shridevi A.; Pujar, Tejaswi V.; ., Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Obstetric emergencies during COVID-19 pandemic pose an enormous challenge to the concerned obstetrician. Risk stratification during obstetric triage will guide in the initial assessment & planning of further management to reduce maternal and fetal morbidity and mortality rates. As the health system adapts to cope with this pandemic, special attention needs to be given to the several moral and ethical dilemmas that may occur during patient care.